Biliary Proliferative Lesions in the Sprague-Dawley Rat: Adverse/Non-adverse. (July 2014) - Hailey, James R.; Nold, James B.; Brown, Roger H.; Cullen, John M.; Holder, Julie C.; Jordan, Holly L.; Ennulat, Daniela; Miller, Richard T.
Whether biliary proliferative lesions in nonclinical species are predictive of potential hepatotoxicity in humans depends, at least in part, on the nature and severity of such changes in the nonclinical species. We reviewed published literature (clinical and nonclinical) and experimental data from rat toxicology studies conducted by GlaxoSmithKline and the National Institute of Environmental Health Sciences' National Toxicology Program in an effort to better characterize the relative risk of hepatobiliary effects in humans. Available evidence supports the interpretation that minimal "typical" appearing bile duct hyperplasia limited to the portal triads may be considered non-adverse in the rat and is of little to no concern to humans. The toxicological relevance of mild to moderate "typical" hyperplasia is less certain, and may be considered adverse in the rat and potentially pose a risk for humans, particularly if accompanied by evidence of hepatobiliary injury or functional compromise. In addition, any proliferative lesion that includes atypical or dysplastic epithelial changes, oval cell proliferation, and/or significant extension beyond the portal tracts is considered more ominous and may be considered adverse in the rat.